Perencanaan Strategis Sistem Informasi Menggunakan Metode Tozer Pada PT Berita Bali Media - Ni Wayan Krisantari Dewi; I Gede Juliana Eka Putra; I Putu Agus Swastika (Prosiding, 2022)
PT Berita Bali Media does not yet have a strategic information system that can assist organizations in developing information systems to help achieve the vision, mission, and organizational goals in the future. On this basis, strategic planning of information systems is needed which in the future can support the information systems needed by PT Berita Bali Media. This study aims to carry out strategic planning of information systems at PT Berita Bali Media.The method used in strategic planning of this information system is the tozer method. This method has 5 phases of strategic planning. The tools used in this research are SWOT, Value chain, Five force competitive model, CSF, PEST, and McFarlan Grid's. Information system strategic planning using the tozer method at PT Berita Bali Media produces a portfolio of information systems obtained from the results of CSF, SWOT, PEST, analysis Value Chain, and McFarlan Grid's. In the information system portofolio there are 4 new information systems, and 12 continued information systems.